Polymerase chain reaction of dried blood spots to detect parasite DNA in individuals with lymphatic filariasis - Singh, Balbir; Cox-Singh, Janet (1999)
Lymphatic filariasis caused by Brugia malayi has traditionally been detected in the blood of infected individuals by microscopy.Screening for blood-stage microfilaria (mf) by microscopy is labour intensive with user fatigue and poor specimen handling responsible for false negative results. Recently a method to detect the DNA from circulating microfilaria using the polymerase chain reaction(PCR) has been described (Lizotte et al., 1994 ). However,the specimen collection method described was unsuitable for routine screening in field situations.The aim of the study reported here was to adapt the PCR method to a simple blood spot sampling and DNA extraction method suitable for remote areas without compromising the sensitivity of PCR. Blood spots were collected from individuals in Kelantan and Terengganu to optimise the technique. A one tube DNA extraction method was developed and coupled to a nested PCR assay that was field tested on an endemic community in Sabah. There was 100% sensitivity when comparing PCR to microscopy but only 70% sensitivity when comparing microscopy to PCR. The increased sensitiyity of PCR coupled with simple sample collection and DNA extraction provides a valuable alternative to microscopy for detecting B. malayi positive individuals in endemic regions of the world.